FORMASI KARAKTER SISWA SEKOLAH DASAR MELALUI IMPLEMENTASI NILAI-NILAI KRISTIANI: ANALISIS BUDAYA SEKOLAH KRISTEN - Rini Adiyati; Utomo, Yunatan Krisno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the character formation of elementary school students through the implementation of Christian values, with a particular focus on Christian school culture as the primary pedagogical medium. Employing a qualitative approach with a descriptive case study design, the research was conducted at SD Daniel Creative School Semarang. Data were collected through observation, semi-structured interviews, and documentation involving the principal, teachers, students, and parents, and were analyzed using the interactive model of Miles, Huberman, and Saldana. The findings reveal that character formation becomes more effective when Christian values such as love, discipline, integrity, responsibility, and service are internalized through the school’s vision, institutional culture, hidden curriculum, learning practices, teacher exemplarity, and family involvement. Christian school culture functions as a transformative space in which Christian values are embodied as students’ lived practices. This study concludes that the effectiveness of character education in Christian elementary schools depends on the consistent, contextual, and holistic integration of Christian values into school culture.